TWITTER SEBAGAI MEDIA PROMOSI WISATA KOTA SEMARANG - Iva Anjar Pawestri (An-Nida : Jurnal Komunikasi Islam, 2014)
Abstract: Keywords Social Media, Social Connected, Marketing. The concept of marketing experienced a revolution from the vertical system to the horizontal system as a solution to the era of web 2.0 adapted. Effecient of using social is a reason of the concept of marketing in the era of web 2.0. The use of social media twitter and facebook in marketing activities is able to make new innovations in promoting a product. The online social community is very effective in creating and maintaining new avenues of marketing in the era of web 2.0. By its realtime, without the constraints of distance, wihout limita- tion of time, so without the need for face to face discussions and interactions, it still runs. In 12Cs marketing mix will only be successful if there is a current that flows as a result of social connectivity. Tourism promotion of Semarang, twitter account @wisatasemarang is an alternative media to promote. Abstract Konsep pemasaran mengalami revolusi dari sistem vertikal menjadi sistem horisontal sebagai solusi adaptasi dengan era web 2.0. Efesiensi penggunaan social connected merupakan alasan konsep pemasaran di era web 2.0. Peng- gunaan media sosial twitter atau facebook dalam kegiatan pemasaran yang dapat menjadikan inovasi baru dalam mempromosikan suatu produk. Komunitas sosial online sangat efektif dalam menciptakan dan mempertahankan jalan baru pemasaran di era web 2.0. Dengan sifatnya yang realtime, tanpa batasan jarak, tanpa batasan waktu, sehingga tanpa perlu bertatap muka diskusi dan interaksi akan terus berjalan. Dalam 12Cs marketing mix hanya akan berhasil dilakukan apabila ada arus konektivitas yang mengalir akibat social connected. Dalam kegiatan promosi pariwisata Semarang, media sosial akun twitter @wisata Semarang merupakan media alternatif promosi wisata Semarang.